2022
DOI: 10.1093/burnst/tkab050
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width/albumin ratio and 90-day mortality after burn surgery

Abstract: Background Red cell distribution width (RDW) and serum albumin concentration are associated with postoperative outcomes. However, the usefulness of the RDW/albumin ratio in burn surgery remains unclear. Therefore, we evaluated the association between RDW/albumin ratio and 90-day mortality after burn surgery. Methods Between 2013 and 2020, a retrospective review of patients in a burn intensive care unit (ICU) was performed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…In this study, the discriminating ability of RDW/ALB for all-cause mortality was significantly superior to RDW in younger, healthier, and less severely ill patients by comparative analysis of ROC curves. The ROC curves analysis also indicated that RDW/ALB ratio had better predictive power for mortality than RDW in patients undergoing burn surgery and with acute respiratory distress syndrome [ 12 , 43 ]. ALB was widely applied to assess the nutritional status and reflect the systemic inflammation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the discriminating ability of RDW/ALB for all-cause mortality was significantly superior to RDW in younger, healthier, and less severely ill patients by comparative analysis of ROC curves. The ROC curves analysis also indicated that RDW/ALB ratio had better predictive power for mortality than RDW in patients undergoing burn surgery and with acute respiratory distress syndrome [ 12 , 43 ]. ALB was widely applied to assess the nutritional status and reflect the systemic inflammation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation failed to be corroborated in another population [ 10 ], which may be due to the population heterogeneity. RDW/albumin (ALB) ratio is a new combined parameter that can predict mortality in patients undergoing burn surgery, and patients with diabetic ketoacidosis [ 11 , 12 ]. Diabetes-related complications were associated with an increased inflammatory burden [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have been conducted with the idea that RAR may provide better results in determining the prognosis of diseases compared to the individual evaluation of either parameter in this ratio [13][14][15]. We conducted the current study for the same purpose, and to our knowledge, our study is the first to determine the predictive ability of RAR in the prognosis of ABP.…”
Section: Discussionmentioning
confidence: 94%
“… 21 , 22 The RDW‐to‐albumin (RA) ratio is a novel inflammatory biomarker, 23 which has previously been used to assess the prognosis of patients with stroke 22 and aortic aneurysms. 23 , 24 We hypothesized that the use of RDW in combination with albumin may be a potential predictor of cancer mortality. In the present study, we assessed the prognostic value RA ratio in predicting cancer mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin not only exerts anti‐inflammatory effects but also reduces oxidative stress and inhibits apoptosis of endothelial cells 21,22 . The RDW‐to‐albumin (RA) ratio is a novel inflammatory biomarker, 23 which has previously been used to assess the prognosis of patients with stroke 22 and aortic aneurysms 23,24 . We hypothesized that the use of RDW in combination with albumin may be a potential predictor of cancer mortality.…”
Section: Introductionmentioning
confidence: 99%